A Conceptual Study on Role of Rasayana in Geriatric Health Care - Heena; Fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2023)
Introduction -Aging refers to degeneration at tissue level. It leads to a gradual decrease in physical and mental capacity. The concept of anti aging is described in Ayurveda as Rasayana, which aims at maintaining excellent physical and mental health in old age through a combination of nourishing diet, wholesome activities and gentle herbs. Material & methods –All classical texts and modern texts including paper, articles were reviewed. Results-The fundamental tissues like Dhātu, Agni, Srotas etc. of human body leading to prevention of aging, improvement in bodily strength, mental ability and hence providing resistance against diseases. One can attain not only longevity alone through Rasayana but also memory, intelligence, youthfulness, excellence of lusture, complexion, mastery over phonetics, resistance and immunity against diseases.Discussion- As elderly people are more susceptible to several chronic diseases also, therefore it is need of study on rasayana therapy for improving the expectancy and quality of life in geriatric health.